2011
DOI: 10.1258/jtt.2010.100322
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of mobile phone text messaging in clinical and healthy behaviour interventions

Abstract: We reviewed the literature on the use of text messaging for clinical and healthy behaviour interventions. Electronic databases were searched in December 2009 using keywords related to text messaging and health interventions. The final review included 24 articles. Of those, seven covered medication adherence, eight discussed clinical management and nine reported on health-related behaviour modification. Sixteen were randomized controlled trials (RCT), five were non-controlled pre-post comparison studies and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
161
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 40 publications
2
161
0
4
Order By: Relevance
“…[7][8][9][10] In a review of seven intervention studies, including four randomized trials, text messaging showed significant promise for improving adherence rates. 7 Controlled evaluations of SMS-based appointment reminders implemented in several countries, including Australia, Brazil, China and the United Kingdom, gave mixed results.…”
Section: Impact On Outcomes and Healthcare Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] In a review of seven intervention studies, including four randomized trials, text messaging showed significant promise for improving adherence rates. 7 Controlled evaluations of SMS-based appointment reminders implemented in several countries, including Australia, Brazil, China and the United Kingdom, gave mixed results.…”
Section: Impact On Outcomes and Healthcare Costsmentioning
confidence: 99%
“…[7][8][9][10] In a review of seven intervention studies, including four randomized trials, text messaging showed significant promise for improving adherence rates. 7 Controlled evaluations of SMS-based appointment reminders implemented in several countries, including Australia, Brazil, China and the United Kingdom, gave mixed results. 9 In a recent randomized trial, both text-message reminders and live telephone calls improved attendance rates for chronic disease follow-up among patients in Malaysia, with no statistically significant differences in impact between the two communication methods.…”
Section: Impact On Outcomes and Healthcare Costsmentioning
confidence: 99%
“…An emerging literature is beginning to provide a solid theoretical and empirical basis for intervention design 24. A variety of techniques have been used: tailoring of text messages to the target group, making texts interactive, information giving, individually tailored advice, self‐monitoring of the behaviour to be changed and goal setting 13, 25, 26, 27, 28. An important recommendation is to vary the number and timing of text messages to fit the target behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…A few systematic reviews have reported positive behavioural trends through SMS-based interventions (14)(15)(16)29) ; however, the evidence documented is inconclusive due to methodological limitations and variations in study designs, settings, populations, length of intervention, SMS delivery intensity, sample size and outcome measures. Text messaging demonstrated only early efficacy in most studies and its long-term efficacy remains to be determined.…”
Section: Discussionmentioning
confidence: 99%